Pengetahuan dan Tindakan Ibu dalam Mengatasi Kesulitan Makan terhadap Status-Gizi Anak (2-5 Tahun) - Mariani, Mariani; Hartono, Antonius Sri; Afif, Irfani (Jurnal Nutrire Diaita (Ilmu Gizi), 2011)
AbstractDifficulties eating factors often experienced by approximately 25 % of children’s, and the number will be increase about 40-70 % in children born prematurely or with chronic disease. The aims of this study was to know the relationship of nutrition knowledge of mothers and mothers action in overcoming adversity to eating children (2-5 years old) on the nutritional status of children in the neighborhood health center Sedap Malam RW 09 Sub Mekarjaya Depok II. This is a descriptive study with cross-sectional design. The population in this study are mothers with children under-five who have weigh their children in neighborhood health center, and we got the total sample are 50 respondents. The results shows that most of respondents were in the education level of high school graduates (54 %), having enough knowledge of nutrition ( 60 % ), has good action in dealing with difficulty eating in children (64 %), good food intake for children (76 %) and partly of the children has a good nutritional status ( 90 % From the chi-square test we found that there is significant association between maternal nutrition knowledge and action to overcome difficulty eating children (χ 2 = 11.595, p <0.05). There is no significant relationship between the acts of a mother and a  nutritional intake of children’s (χ 2 = 0.490, p > 0.05). There is no significant relationship between nutritional intake of children’s and nutritional status of children’s (χ2 = 0.780, p ≥ 0.05). Need more nutrition counseling for mothers to increase their nutrition knowledge. Keywords: mother knowledge, nutritional intake, nutritional status  AbstrakFaktor kesulitan makan sering dialami oleh sekitar 25% anak, dan jumlahnya akan meningkat sekitar 40-70% pada anak yang lahir premature atau dengan penyakit kronik. Penelitian ini bertujuan untuk mempelajari hubungan pengetahuan gizi ibu dan tindakan ibu dalam mengatasi kesulitan makan anak (2-5 tahun) terhadap status gizi anak di posyandu Sedap Malam RW 09 Kelurahan Mekarjaya Depok II. Penelitian ini bersifat deskriptif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah ibu-ibu yang memiliki anak balita yang menimbangkan anaknya di posyandu, dan jumlah sampel sebanyak 50 responden. Hasil penelitian menunjukkan bahwa sebagian besar tingkat pendidikan responden adalah lulusan SLTA (54%), memiliki pengetahuan gizi cukup (60%), memiliki tindakan baik dalam mengatasi sulit makan pada anak (64%), asupan makan anak baik (76 %)dan sebagian besar anak memiliki status gizi baik (90%). Dari hasil uji chi-square didapat hubungan yang bermakna antara pengetahuan gizi dengan tindakan ibu mengatasi sulit makan anak (χ 2 =11,595; p < 0,05). Tidak ada hubungan bermakna antara Tindakan ibu dengan asupan gizi anak (χ 2 = 0,490 ; p > 0,05). Tidak ada hubungan bermakna antara Asupan gizi anak dengan status gizi anak (χ2 = 0,780; p > 0,05). Pengetahuan gizi ibu dan tindakan ibu mempengaruhi dalam mengatasi kesulitan makan anak, oleh karenanya perlu adanya dilakukan penyuluhan kepada ibu tentang cara mengatasi kesulitan makan pada anak. Kata Kunci: Pengetahuan Ibu, Asupan Makan, Status Gizi